ARMENIAN FOREIGN POLICY: OORDINATING THE INTERESTS OF THE U.S., THE EU,AND RUSSIA - MIKAELIAN, Hrant (CENTRAL ASIA AND THE CAUCASUS, 2009)
The severe depression of the 1990s that served the background for Armenia’s foreign policy determined many of its outstanding features. Isolation and blockade forced the country to turn to the Armenian diaspora. The landlocked country living in “neither peace nor war” could not attract the West; however it established effective cooperation with Russia and Iran. In recent years it has widened its contacts with the European Union and the United States. This helped the Armenians to survive in the hardest first post-Soviet years. The Soviet successor states (with the exception of the Baltic countries) were ill-prepared to conduct an independent foreign policy: the statehood experience and skills of coexistence had largely been lost in the region. Over the 70 years the three Caucasian states (Azerbaijan, Georgia and Armenia) were detached from their immediate neighbors (Turkey and Iran) they cooperated solely with Russia—it was not until the 1990s that they returned to their natural regional environment. The region borders on Russia, Turkey, and Iran (in fact, on the Greater Middle East and Central Asia), while on the other side of the Black Sea it finds itself at the doors of the European Union. This explains why each of the countries has had to look for an acceptable balance of forces to protect its interests. Their newly acquired independence suggested that the three Caucasian states build their foreign policies from scratch. The three republics preferred to indulge themselves in the myths of their advantageous geographic location1 and the possibility of “making the best of both worlds” by living on their own resources—it was generally believed that the Center had hindered their development. Reality proved to be different: the region plunged into an abyss of economic crisis and post-Soviet chaos; Armenia suffered more than its neighbors: its standard of living took a nosedive.